Endosulfine, an endogenous peptidic ligand for the sulfonylurea receptor: purification and partial characterization from ovine brain. - Virsolvy-Vergine, A (1992)
Antidiabetic sulfonylureas act through receptors coupled to ATP-dependent potassium channels. Using the binding of [3H]glibenclamide, a highly potent sulfonylurea, to rat brain membranes to follow the purification procedure, we extracted from ovine brain, purified, and partially characterized two peptides that are endogenous ligands for the central nervous system sulfonylurea receptors. These peptides, referred to as alpha and beta endosulfine, differ by their isoelectric points, the beta form being more basic. Each form of endosulfine is recognized equally by the sulfonylurea receptors from the central nervous system and from insulin-secreting beta cells. In the same concentration range that is active on the receptors, beta endosulfine releases insulin from a beta-cell line. Endosulfine is a good candidate for being implicated in the physiology of beta cells and their disorders (e.g., type II diabetes) and in certain pathologies related to modifications of ion fluxes.